SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/110518-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Capillary Pressure Curves Obtained Using Traditional Centrifuge and Magnetic Resonance Imaging Techniques

Abstract: The current study is a comparison trial of a new Magnetic Resonance Imaging (MRI) method for acquiring capillary pressure versus traditional techniques. This study is meant to evaluate the methodology and workflow by performing measurements at the University of New Brunswick, Canada and on-site with CoreLab in Houston, TX, USA. This study focuses on gas-brine primary drainage capillary pressure systems.Traditional centrifuge capillary pressure measurements require the fluid(s) to reach equilibrium at many diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…A good account on practical aspects and a review of MRI techniques applicable for petrophysical measurements is given in Mitchell et al (2013). Chen and Balcom (2005), Green et al (2007) proposed to apply a T 1 -based SPRITE technique (single-point ramped imaging with T 1 enhancement) to determine fluid saturation along the length of a centrifuged rock core. Composite capillary curves were constructed in assumption of core homogeneity and known capillary pressure as a function of position.…”
Section: Concept Of Relative Permeability With Spatially Resolved Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…A good account on practical aspects and a review of MRI techniques applicable for petrophysical measurements is given in Mitchell et al (2013). Chen and Balcom (2005), Green et al (2007) proposed to apply a T 1 -based SPRITE technique (single-point ramped imaging with T 1 enhancement) to determine fluid saturation along the length of a centrifuged rock core. Composite capillary curves were constructed in assumption of core homogeneity and known capillary pressure as a function of position.…”
Section: Concept Of Relative Permeability With Spatially Resolved Nmrmentioning
confidence: 99%
“…Here we aim to compare this CM-NMR approach to NMR relaxation-based estimates proposed by AlGhamdi et al (2013). We modified the latter for use with centrifuge (CM-NMR-T 1 ), which enables the acquisition of multiple data points in a single experiment similarly to Green et al (2007). NMR longitudinal relaxation is used to avoid influence of internal gradients effects common in saturated sandstones.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement was T 2 relaxation time which was obtained by CPMG method (Green et al, 2008). The NMR equipment used for these measurements had a frequency of 2.4 MHz, which is almost the same as the frequency used in logging NMR.…”
Section: Evaluation Of Pore Diameters By Nmrmentioning
confidence: 99%
“…By using MRI to image the distributed water saturation in a core plug after centrifugation, Green et al (2007) recently reported the lack of S w = 1.0 at the outflow face. They speculated that 100% saturation at the outlet was obtained only in a very thin layer, which could not be resolved at the spatial resolutions of the MRI (<1 mm).…”
Section: The Outlet Boundary Conditionmentioning
confidence: 99%